DNA methylation and expression of imprinted genes are associated with the viability of different sexual cloned buffaloes. (27th October 2017) - Ruan, Z; Zhao, X; Qin, X; Luo, C; Liu, X; Deng, Y; Zhu, P; Li, Z; Huang, B; Shi, D; Lu, F
Contents: The DNA methylation of imprinted genes is an important way to regulate epigenetic reprogramming of donor cells in somatic cell nuclear transfer (SCNT). However, the effects of sexual distinction on the DNA methylation of imprinted genes in cloned animals have seldom been reported. In this study, we analysed the DNA methylation status of three imprinted genes ( Xist, IGF2 and H19 ) from liveborn cloned buffaloes (L group, three female and three male), stillborn cloned buffaloes (S group, three female and three male) and natural reproduction buffaloes (N group, three female and three male), using bisulphite sequencing polymerase chain reaction (BS‐PCR). The expression levels of these imprinted genes were also investigated by quantitative real‐time PCR (QRT‐PCR). The DNA methylation levels of H19 were not significantly different among the groups. However, the Xist in female and IGF2 in male of the S group were found to be significantly hypomethylated in comparison with the same sexual buffaloes in L group and N group ( p  <   .05). Furthermore, the expression levels of Xist, IGF2 and H19 in the stillborn female cloned buffaloes of S group were significantly higher than that of the female buffaloes in the L group and N group ( p  <   .05). The expression levels of IGF2 and H19 in the stillborn male cloned buffaloes in the S group were significantly higher than that of the male buffaloes in the L group and N group ( p  <   .05). These results indicate that Xist may be associated with the viability of female cloned buffaloes, and IGF2 may also be related to the viability of male cloned buffaloes.